Polymer Materials & Waste Industrial Products might be Dangerous for Destroying the Forests in Türkiye: An Overview of Climate Changing in Viewpoint of Bio Thermochemical Analysis - (:unkn) unknown (AMG Transcend Association, 2023)
Cleaning and saving the forest is related to managing and utilizing forests' biodiversity, productivity, and considering the relevant environment. Plastic waste management is now seen as an important goal for sustainable forest use as well as incorporating recycled plastics into products. Another way that industries impact wildlife and forests is by releasing additives such as industrial gases, organic & inorganics materials, plastic & resins, fertilizers & alkalies, and chlorine. Polymer wastes manage to enter into and harm numerous biological functions of animals. In this work, the concept of sustainable Türkiye's forest practices and addressing the impact of plastic waste on the forests and environment before and during the COVID-19 epidemic are discussed along with current sources of those mentioned materials wastes that manage to enter the environment. Through this work, the data of bio thermochemistry and thermodynamics calculations of such polymers have been investigated to exhibit the range of sustainability and unsustainability of those mentioned polymers and resins in the environment due to forest climate change. Since the Türkiye chemical industry is one of the most important industrial factors, their production contributes in similar proportions to greenhouse gas emissions. Interestingly, low data on energy usage in the factories and chemical industry is available in the public domain. Ethylene production is the major product in terms of the production volume of the petrochemical industry. Nitrogenous fertilizer production is a very energy-intensive industry, producing a variety of fertilizers and other nitrogen compounds. In addition, ammonia, chlorine, and caustic soda are the most important mediator chemical material used as the main compound for almost all products.